2022
DOI: 10.3390/mi13040519
|View full text |Cite
|
Sign up to set email alerts
|

Design of an Integrated Near-Infrared Spectroscopy Module for Sugar Content Estimation of Apples

Abstract: An integrated near-infrared (NIR) spectroscopy prototype module for sugar content estimation of apples is presented. Since this is the first attempt to design an integrated NIR spectroscopy module, we followed the design process as follows. First, we estimated the sugar content of apples using a tungsten halogen light source and a 700 nm–1000 nm NIR spectrometer with a 10 nm wavelength resolution and a 16b analog-to-digital converter (ADC) resolution. Second, we determined the most effective wavelengths among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Several studies have shown that NIR can predict individual sugars and total sugar content with high accuracy, making it a promising tool for the fruit industry [78,[185][186][187][188][189]. This suitability of NIR spectroscopy was demonstrated relatively early.…”
Section: Sugar Profilementioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that NIR can predict individual sugars and total sugar content with high accuracy, making it a promising tool for the fruit industry [78,[185][186][187][188][189]. This suitability of NIR spectroscopy was demonstrated relatively early.…”
Section: Sugar Profilementioning
confidence: 99%
“…The interest in this analysis continues in contemporary literature. For example, a design of an integrated NIR spectroscopy module for estimating sugar content in apples was recently presented by Byun [187]. The design process involved selecting effective wavelengths and reducing the analog-to-digital converter resolution.…”
Section: Sugar Profilementioning
confidence: 99%
“…Near infrared light is between visible and medium infrared light and has a wavelength range of 780nm-1100nm. The near infrared spectroscopy can be used to detect the sugar content of apple with high precision [6]. According to the theory of molecular spectroscopy, when the molecule of a substance is in the ground state, it is the most stable.…”
Section: Apple Sugar Content and Apple Spectrummentioning
confidence: 99%